2021
DOI: 10.3389/feart.2021.681312
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of (Sub-)Hourly Rainfall in Convection-Permitting Climate Simulations Over Southern Sweden From a User’s Perspective

Abstract: To date, the assessment of hydrological climate change impacts, not least on pluvial flooding, has been severely limited by i) the insufficient spatial resolution of regional climate models (RCMs) as well as ii) the simplified description of key processes, e.g., convective rainfall generation. Therefore, expectations have been high on the recent generation of high-resolution convection-permitting regional climate models (CPRCMs), to reproduce the small-scale features of observed (extreme) rainfall that are dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 46 publications
1
19
0
Order By: Relevance
“…HCLIM3 also overestimates the precipitation events of more than 5 mm (R5mm) by around 60 % (5 % over Sweden), while HCLIM12 underestimates these events by 43 %-69 %. Also, Lind et al (2020) and Olsson et al (2021a) found mostly positive biases for hourly values over the 95th percentile in HCLIM3 and underestimation of the percentile values by HCLIM12.…”
Section: Evaluation Of Heavy Hourly Precipitationmentioning
confidence: 91%
See 4 more Smart Citations
“…HCLIM3 also overestimates the precipitation events of more than 5 mm (R5mm) by around 60 % (5 % over Sweden), while HCLIM12 underestimates these events by 43 %-69 %. Also, Lind et al (2020) and Olsson et al (2021a) found mostly positive biases for hourly values over the 95th percentile in HCLIM3 and underestimation of the percentile values by HCLIM12.…”
Section: Evaluation Of Heavy Hourly Precipitationmentioning
confidence: 91%
“…HCLIM12 and ERA5 also underestimate the observed intensities of the 99.9th percentile events throughout the day. Previously, Belušić et al (2020), Lind et al (2020), andOlsson et al (2021a) have shown that HCLIM3 improved the representation of the diurnal cycles of mean precipitation as well as the 90th and 99th percentiles compared to HCLIM12.…”
Section: Evaluation Of Heavy Hourly Precipitationmentioning
confidence: 99%
See 3 more Smart Citations